ANALISIS PENGARUH FAKTOR INTERNAL DAN EKSTERNAL PADA NON PERFORMING LOAN (NPL) (Studidi Empiris Bank Umum Yang Terdaftar di BEI Periode 2017-2020) - Muchammad Azrial Akbar; Erma Setiawati (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
This study aims to determine the effect of Capital Adequacy Ratio (CAR), Loan to Deposit Ratio (LDR), Net Interest Margin (NIM), Operational Cost of Operating Income (BOPO), SBI Interest Rate, Inflation, Company Size, and Return On Assets ( ROA) simultaneously or partially on Non Performing Loans (NPL) in Commercial Banking Companies listed on the Indonesia Stock Exchange (IDX). The research population is general banking companies listed on the Indonesia Stock Exchange (IDX) in 2017-2020 as many as 47 companies with purposive sampling technique obtained 9 companies. The data analysis method used is multiple linear regression with a significance level of 0.005. The results showed that the Capital Adequacy Ratio (CAR), Inflation, and Return On Assets (ROA) had an effect on Non Performing Loans (NPL). Meanwhile, Loan to Deposit Ratio (LDR), Net Interest Margin (NIM), Operating Income Operating Expenses (BOPO), SBI Interest Rate, and Company Size have no effect on Non-Performing Loans (NPL).